Evaluation of Origin and Conformation of Excellent Cows with Long Productive Lives - Berta, Attila; Béri, Béla (Acta Agraria Debreceniensis, 2005)
In the last few decades a new intensive milking stock has developed as a result of breed-converter crossing in Hungary. Beside this reproduction biology of the population was affected adversely by the keeping-, and feeding technology. Serviceable lifetime has shortened and service period has lenghtened. Whereas profitable milk production needs cows with longer productive life, larger life-time production. In our work we analysed the productivity-, and reputation parameters of the 200 highest lifetime-productivity cows of Hungary. We found that inheritance has not got important role in the serviceable lifetime. Adaptability and good constitution of Holstein-friesian is proved by the fact that cows with large life-time production are reared in large plants, some of them in large stocks, industrial environment. We found during the analysis of reputation parameters that these prominent cows mostly have deeper body, higher dairy form, higher rear udder, smaller foot angle. We found some weak connection between the milk production and the reputation. Loose correlations between useful material content and some linear traits were found.